Application of 5% acetic acid as a diagnostic adjunct in the detection of oral potentially malignant disorders - Rimal, Jyotsna; Regmee, Pragya; Shrestha, Ashish; Upadhayaya, Paricha; Shrestha, Ashish (Journal of Kathmandu Medical College, 2023)
Background: Commercial vinegar (acetic acid) can be a good and cost-effective screening tool for Oral Potentially Malignant Disorders (OPMDs) in resource constraint countries.Objectives: To assess the sensitivity, specificity, and accuracy of 5% acetic acid for the detection of epithelial dysplasia in OPMDs.Methods: This study was an analytical cross-sectional study done to assess the diagnostic accuracy. It was done in hospital and field settings from, 2017 January to 2019 February, after ethical approval from IRC of BPKIHS. Convenience sampling technique was used and 114 individuals (57 participants with OPMDs and 57 participants with normal oral mucosa) were included. Acetic acid was applied and allowed to be in contact for one minute. A positive finding (acetowhitening) was designated in a lesion that changed its colour to opaque white, while a negative finding was designated for the lesion that showed no change. This was followed by biopsy and histopathology. Patients who were undergoing extraction at the community camps with normal oral mucosa were included as participants without target condition (OPMD). Sensitivity, specificity, and accuracy were calculated for 5% acetic acid in detecting oral epithelial dysplasia.Results: Total number of patients included in the study was 114. Among the total sample, 54 had dysplasia on histopathological evaluation, 60 did not have dysplasia. Fifty-five patients had positive acetowhitening and 59 patients had negative acetowhitening reaction. The sensitivity, specificity, and accuracy were, 0.759, 0.766, and 0.763 respectively.Conclusions: The sensitivity, specificity, and accuracy of commercially available vinegar in detecting oral epithelial dysplasia are good.